2017
DOI: 10.1080/17436753.2017.1343781
|View full text |Cite
|
Sign up to set email alerts
|

In situ synthesis of polycrystalline cubic boron nitride with high mechanical properties using rod-shaped TiB2 crystals as the binder

Abstract: Polycrystalline cubic boron nitride (PcBN) was sintered in the temperature range of 1050-1650°C under an ultra-high pressure of 5.0 GPa for 20 min using an in situ synthesis method. X-ray diffraction, X-ray photoelectron spectroscopy, scanning electron microscopy and energydispersive spectrometry were used to study the compositional and morphological changes during the synthetic process. The results showed that rod-shaped TiB 2 crystals could be detected at 1150°C, and their quantity increased with sintering t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 42 publications
0
0
0
Order By: Relevance
“…In this study, the change in weight percentage within the BN and TiB2 phases was caused by the firing treatment during specimen formation [45]. The growth of the TiB2 phase can be observed at a firing temperature of 1150˚C and will increase when given a higher firing temperature [50]. However, a study conducted by Tong, et al, (2008) showed that the presence of the BN phase could inhibit the growth of other compound phases [51].…”
Section: Fig 6 Xrd Pattern Of the Crucible Specimens With Various Con...mentioning
confidence: 89%
“…In this study, the change in weight percentage within the BN and TiB2 phases was caused by the firing treatment during specimen formation [45]. The growth of the TiB2 phase can be observed at a firing temperature of 1150˚C and will increase when given a higher firing temperature [50]. However, a study conducted by Tong, et al, (2008) showed that the presence of the BN phase could inhibit the growth of other compound phases [51].…”
Section: Fig 6 Xrd Pattern Of the Crucible Specimens With Various Con...mentioning
confidence: 89%